Factors that affect the dividend performance of ASB at ASNB / Mohd Amir Syafiq Matsahuri and Siti Munirah Mansor - Matsahuri, Mohd Amir Syafiq; Mansor, Siti Munirah (Faculty of Business and Management, 2013)
Amanah Saham Bumiputra (ASB) is one of the most favorable choices when it comes to the unit trust investment. As far as we concern ASB is one of the unit trust investment that paid with the highest dividend towards its holders. However, how many of us are aware with the factors that had taken to be considered for the dividend being paid. Thus, in this study we are emphasizing in the factors that affect dividend performance of ASB. The data collected is provided by the ASNB and processed by the E-Views 7.0 software. The result indicated that GDP and BLR are having significant relationship towards the performance of ASB while CPI did not have any significant relationship. In this study BLR shows the highest coefficient which means, BLR is the factor that influence the most toward the dividend performance. ASNB are therefore recommended to focus on these two factors, but should pay less attention on others factor. In this research as well, we had found that ASNB is lack of young investor.